PERTANGGUNGJAWABAN DIREKSI TERHADAP KEPAILITAN PERSEROAN TERBATAS (STUDI TERHADAP PUTUSAN MAHKAMAH AGUNG No.05/PAILIT/2012/PN/NIAGA.SMG) - FENTY RISKA (PREMISE LAW JURNAL, 2016)
Bankruptcy is a public confiscation upon the Bankrupt Debtor’s whole property which management and settlement are carried out by a Curator under the direction of the Supervisory Judge. The research used judicial normative and descriptive analytic. The consideration of the Commercial Judges as the District Court of Semarang declaring PT. Indonesia Antique to be bankrupt was that is was proved to have two creditors and to be unable to pay the creditors its debts that past due and were collectable, thus, it met the provision stipulated in article 2 of Law No. 37/2004 abut Bankruptcy and PKPU. In addition, the considerations of the Supreme Court judicial panel of the Republic Indonesia stated that, all land confiscated in Bankruptcy Verdict by the Commercial Court at District Court at district Court of Semarang was proved to be the proprientary assets of PT. Indonesia Antique that were used as the collateral for the debts payment of PT. Indonesia Antique to its creditors, and was, therefore, bound to the assets of Bankrupt Estates. Keywords : Liability of Board of Directors, PT (Limited Liability Company), and Bankruptcy